Kudos to APB UiTMCPP specifically and UiTMCPP in general!!! / Mah Boon Yih - Mah, Boon Yih (Academy of Language Studies, 2021)
University Academic Award (UAA 2020) is the most prestigious recognition of academic excellence among the lecturers of Universiti Teknologi MARA (UiTM) since its launching in 2009. The objective of the award is to recognise the academic excellence of those who have centrestaged UiTM at the global arena. A total of 13 categories were nominated. The main categories were Distinguished Academician Award, Most Promising Academician Award, Product Innovation and Commercialization Award, Journal Article Publication Award, Teaching Award, Book Publication Award, and Arts and Creativity Award. Other categories were Academic Leadership Award, Best Researcher Award, Most Prolific Writer Award, Best Speaker Award, e-Learning Award, and Best Supervisor Award. Three UiTM Cawangan Pulau Pinang (UiTMCPP) academic staff received awards at the UAA 2020